Application of the NEOH Framework for Self-Evaluation of One Health Elements of a Case-Study on Obesity in European Dogs and Dog-Owners - Muñoz-Prieto, Alberto; Nielsen, Liza R.; Martinez-Subiela, Silvia; Mazeikiene, Jovita; Lopez-Jornet, Pia; Savić, Sara; Tvarijonaviciute, Asta (Frontiers in Veterinary Science, 2018)
Obesity is a malnutrition disorder of global concern with increasing prevalence driven by underlying societal, economic and environmental mechanisms leading to changed physical activity patterns, eating behaviours and diet compositions in both humans and in their pet-dogs. A questionnaire-based study was carried out as a joint effort across 11 European countries. It was considered a One Health (OH) initiative between scientists from human and animal health sectors aiming to identify factors associated with obesity in dog owners and their dogs. Expected outcomes of this approach included new insights unachievable by single-sector research initiatives, and hence potentially leading to new cross-sectorial solutions. We performed an internal evaluation among the actors of the obesity initiative using the framework for evaluation developed by the “Network for Evaluation of One Health” (NEOH). It served as a case-study for the NEOH consortium to illustrate the application and provide feedback on the utility of the framework. The evaluation was performed by a subgroup of scientists also involved in the obesity study group, and it consisted of: (1) the definition of the initiative and its context, (2) the description of the theory of change, and (3) the qualitative and quantitative process evaluation of operations and supporting infrastructures scored on a scale from 0 to 1. In the One Health operations, the obesity study initiative scored medium high on OH-thinking (0.5) and OH-planning (0.45), and relatively high on OH-working (0.7). The supporting infrastructure score was high for systemic organization (0.8), but low for sharing (0.45) and learning (0.28). The calculated OH-index was 0.29 (on scale 0 to 1) indicating that the full potential of health integration and collaboration was not exploited in the initiative, and the main issue identified was a lack of stakeholder engagement. The OH-ratio of 1.1 indicated equal focus on operations and supporting infrastructures. Hence, the evaluation identified potentially counterproductive as well as beneficial characteristics, which are further discussed in this paper in relation to the expected outcomes. The NEOH framework for evaluation requires that the evaluators have a good understanding of systems thinking and the mechanisms of the health issue targeted by the initiative.